The Theoretical Framework of AmtsÄl in the Qur'an: Enhancing Understanding of Qur'anic Content - Irham, Muhammad; Suryadinata, M.; Hidayat, Taufiq; Arib, Juhrah M.; Mokodenseho, Sabil (Institut Agama Islam Negeri (IAIN) Curup, 2023)
This article aims to analyze the theoretical conception of the science of amtsÄl in the Qur'Än, then its relevance and contribution to the implementation of the contents of the Qur'Än. This study is necessary because the Qur'Än has a strategic position in the movement of the life activities of Muslims. In addition, the Qur'Än is not only valuable reading but also guidance for humans in the aspects of worship, faith, and morals. One of the methods that can be used to understand the verses of the Qur'Än properly, correctly, and comprehensively, one of which is through the sciences of amtsÄl Qur'Än, because in the Qur'Än there are verses matsÄl. This study uses a qualitative method with a library approach. This research found that several things, including: First, the term amtsÄl of the holy Qur'Än is a parable or expression with a beautiful style set by Allah SWT. through the holy Qur'Än in the form of a short, clear, and concise expression to serve as a good role model in order to increase faith in Allah SWT. Second, there are four kinds of amtsÄl, namely amtsÄl qissah, amtsÄl lil hal, amtsÄl al-wasfi and amtsÄl al-i'tibar. While in understanding amtsÄl there are three, namely amtsÄl musarrahah, amtsÄl kaminah, and amtsÄl mursalah. Third, the term amtsÄl of the holy Qur'Än shows several benefits to facilitate its use, namely showing something that is ma'qul into a concrete form, so that it can be felt or easily understood by humans, revealing essences and suggesting something that is not appearing as if it becomes visible, or making the unseen as if it can be witnessed immediately, also provides motivation for things that are liked. The results of the study show that the theoretical conception of the science of amtsÄl Qur'Än has relevance in understanding the content of the verses of the Qur'Än in which there are verses of tamtsÄ«l. This conclusion theoretically contributes to understanding the Qur'an properly and correctly while at the same time being able to ground the teachings that originate from the Qur'Än.